Modeling and analysis of the utilization of common gas resources between Iran and Qatar, considering various scenarios of resource distribution and extraction power: а game theory approach - D. A. Pervukhin; D. Hadi; D. D. Kotov (Современная наука и инновации, 2024)
Oil and gas are the drivers of many economic and production activities, so they have a crucial place in economic growth and development. South Pars/North Dome gas field is the world's largest gas field between Iran and Qatar, which needs to be properly developed and utilized. Iran and Qatar jointly own this field and they have the responsibility to develop appropriate strategies for oil and gas exploitation. This study analyzes four static Nash equilibrium game models and the optimal strategies between Iran and Qatar to exploit their common resource. Iran's extraction capacity is assumed to be affected by international sanctions, which leads to inequality of extraction capacity. The different conditions of the model include "equal resource allocation and equal extractive capacity", "unequal allocation with equal extractive capacity", "equal allocation with unequal extractive capacity" and "unequal allocation with unequal extractive capacity". The results of the study show that in the first two scenarios, in which neither country is sanctioned, both countries must decide not to commit to cooperation. However, in the latter two scenarios, when Iran is under sanctions and has weaker extractive power, it should adopt a cooperative policy, while Qatar should adopt a noncooperative approach. Thus, a country's decision to participate in the exploitation of shared resources depends on its extractive power rather than resource allocation. Consequently, it can be argued that Iran and Qatar's shared gas field, which is unequally divided, is significantly affected by sanctions. Iran's sanctions caused its production capacity to decrease, and it adopted a strategy of cooperation with Qatar. At the same time, Qatar's dominant strategy is non-cooperation. As a result, Iran suffers from exploitation of common resources under sanctions.